High Time Resolution Observation of Solar Radio of A Group Type III And U Burst Associated of Solar Flares Event - Hamidi, Z.S.; Shariff, N.N.M.; Monstein, C. (IJES, 2012)
The results of high time resolution of solar flare type III and U burst at National Space Centre, Sg Lang, Selangor, Malaysia have been reported. We selected data in the meter - wave region solar radio spectral observations of the 2012 March 9th flare. During that period, a strong M 7.9 solar flare was recorded from solar Active Region 1429. It is clearly seen an inverted type occurs between 310 MHz till 384 MHz within 1 second. The group of type III burst also occurred before type U. During this period, M6 solar flare occurred in the active region AR 1429 starting at 03:32 UT and ending at 05:00 UT, with the peak at 04:12 UT. There is also a halo of Coronal Mass Ejections (CMEs) produced shortly after, and is expected to deliver a glancing blow t o the earth’s magnetic field sometime March 16th. In conclusion, we believed that the behavior of type III should be critically understood in order to predict the formation of type U burst. This also approve that the CALLISTO system possible to detect a radio burst signal at a precise time.